Savings-Growth Nexus in Ghana: Cointegration and Causal Relationship Analyses - Pickson, Robert Becker; Enning, Koduah Dawud; Siaw, Anthony (Scientific Research, 2017)
The wide range of controversies surrounding the direction of causality between savings and economic growth necessitated this study. The study was intended to investigate the relationship between gross domestic savings and economic growth in Ghana; with the specific objective of finding whether there exists a long run relationship between them, and it was also intended to ascertain the direction of causality between the two running actors in the study over the period of 1972 to 2013. The study employed Johansen cointegration test to reveal no long run relationship between gross domestic savings and economic growth in Ghana. This necessitated the usage of the VAR technique to estimate the short run relationships. The finding was that there exists a unidirectional line of causation running from gross domestic savings to economic growth in Ghana. It is strongly recommended therefore that the Bank of Ghana will use the monetary policy instruments to influence and advise the commercial banks on the need to peg the deposit rate relatively higher at least equal or little above the existing interest rate. This is because the deposit rate is the opportunity cost of money demand for other purposes.
Keywords: Gross Domestic Savings; Economic Growth; Ghana